The Heavens and Hells of Scottish Literature: An Interview with Alasdair Gray - Argueso San Martin, Paula (Complutense Journal of English Studies, 2021)
On the occasion of the publication of the Contemporary Scottish Urban Literature CJES Special Issue, this interview to Scottish writer Alasdair Gray, one of the last he gave, aims to celebrate Gray’s work and to emphasise his role as a crucial influence for the contemporary Scottish writers whose work features in this special issue. In a very personal manner, Gray strings together reflections on contemporary politics, discusses the role of the local and the national in his work and addresses questions on the construction of his male characters in a discourse which ultimately highlights the determining role of Gray’s socio-political and cultural environment plays his art. Moreover, Gray talks about the artists he was exposed to as a kid and the manner in which these were influential. Considering its wide scope, this interview may serve as a guide to better understand Gray’s work, the reasons why he merges fantasy and reality in his novels and short stories, and the socio-political breeding ground of his socialist and civic nationalist political agenda.